Candida albicans Sap6 Initiates Oral Mucosal Inflammation via the Protease Activated Receptor PAR2 - Kumar, Rohitashw; Rojas, Isolde Gina; Edgerton, Mira (Frontiers in Immunology, 2022)
Candida albicans secreted aspartyl protease Sap6 contributes to fungal virulence in oral candidiasis. Beside its protease activity, Sap6 contains RGD (RGDRGD) motif required for its binding to host integrins. Sap6 activates immune cells to induce proinflammatory cytokines, although its ability to interact and activate human OECs remain unknown. Addition of purified recombinant Sap6 (rSap6) to OECs resulted in production of IL-1β and IL-8 cytokines similar to live hyphal C. albicans. OECs exposed to rSap6 showed phosphorylation of p38 and MKP1 and expression of c-Fos not found with C. albicans Δsap6, heat-inactivated Sap6, or rSap6ΔRGD. Heat inactivated rSap6 was able to induce IL-1β but not IL-8 in OECs, while rSap6ΔRGD induced IL-8 but not IL-1β suggesting parallel signaling pathways. C. albicans hyphae increased surface expression of Protease Activated Receptors PAR1, PAR2 and PAR3, while rSap6 increased PAR2 expression exclusively. Pretreatment of OECs with a PAR2 antagonist blocked rSap6-induced p38 MAPK signaling and IL-8 release, while rSap6ΔRGD had reduced MKP1 signaling and IL-1β release independent from PAR2. OECs exposed to rSap6 exhibited loss of barrier function as measured by TEER and reduction in levels of E-cadherin and occludin junctional proteins that was prevented by pretreating OECs with a PAR2 antagonist. OECs treated with PAR2 antagonist also showed reduced rSap6-mediated invasion by C. albicans cells. Thus, Sap6 may initiate OEC responses mediated both through protease activation of PAR2 and by its RGD domain. This novel role of PAR2 suggests new drug targets to block C. albicans oral infection.